Treatment of West syndrome: A comparison of the efficacy of adrenocorticotropic hormone and corticosteroids (Research, Society and Development, 2024)
West Syndrome, as known as infantile spasms, is an epileptic encephalopathy that primarily manifests through muscle spasms, developmental delay, and hypsarrhythmia on EEG. Inadequate treatment can lead to long-term cognitive and behavioral impairments. The main therapies involve the use of adrenocorticotropic hormone (ACTH) and prednisolone (adrenal cortex hormones), both showing similar efficacy in controlling spasms and resolving hypsarrhythmia. Comparative studies show varied results. In the short term, some studies do not indicate a level of superiority between prednisolone or ACTH, while in the long term, ACTH may be more effective in preventing relapses, though without significant disparity between the two treatments. Prednisolone, however, is more accessible, making it a cost-effective option, especially in countries with fewer resources, where ACTH treatment may be unfeasible due to its high cost. Thus, both treatments offer well-established solutions, with prednisolone standing out for its cost-benefit ratio. The objective of the presente study was to analyze clinical trials on West Syndrome, comparing treatments with ACTH and corticosteroids, through na integrative review.